Cuidados em saúde na população não-binária: um estudo exploratório com identidades que transcendem a binaridade de gênero - Alminhana, Vanessa Oliveira (2020)
To address the issue of access to health by trans and non-binary people, the concepts of sex, gender, binary and non-binarity are initially developed. The study proposal is justified by the frequent exclusion of non-binary people in health-related research, which generates ignorance and professional unpreparedness in meeting these demands. As a result, non-binary people tend to seek health treatments through self-medication or peer care, which makes this population even more vulnerable. This study aimed to explore the demands and barriers faced in accessing health care by people who identify themselves as non-binary in relation to gender, as well as knowing their life experiences. With this, the concepts of sex, gender, binarity and non-binarity are approached and developed, to then enter the theme of access to health and the resulting confrontations, using the Queer Theory as the basis of understanding. This research is an exploratory study, carried out through semi-structured interviews, with five self-declared participants with a non-binary gender, invited based on a convenience sample and the snow ball technique, where one person can go indicating another consecutively. The data were analyzed using the Thematic Analysis method. This research was approved by the Ethics Committee of the Pontifical Catholic University of Rio Grande do Sul under registration 09740419.0.0000.5336. From the found patterns, 3 categories were raised: 1. Binary access, 2. Professional unpreparedness and 3. Coping micropolitics. The lack of knowledge about nonbinarity, motivated by a binary social structure that culminates in professional unpreparedness, were factors unanimously pointed out by the interviewees. Coping micropolitics ranged from avoiding victimization in contexts of health, self-medication and / or peer care, to a high level of knowledge of their demands and rights. Finally, within the third category, a subcategory entitled Good Healthcare practices was raised, where committees, associations and standards of affirmative and qualified care for the health of the trans, non-binary and non-conforming gender population were listed.